Storage Stability of Complete Feed Wafers Containing Mangrove Fruit and Palm Fatty Acid Distillate: Physical Properties and In Vitro Rumen Fermentation - Zaitul Ikhlas; Novirman Jamarun; Yoshiyuki Murata (Andalasian Livestock, 2026)
This study aimed to evaluate the effects of storage duration on the physical properties of complete feed wafers supplemented with mangrove fruit as a tannin source and palm fatty acid distillate (PFAD) as an energy source, as well as in vitro rumen fluid characteristics. A completely randomized design was used with four storage duration treatments: 15 days (T1), 30 days (T2), 45 days (T3), and 60 days (T4), with five replications. The feed ingredients consisted of fermented sugarcane tops, Tithonia diversifolia, concentrate, mangrove fruit, and PFAD, which were processed into complete feed wafers. The observed parameters included the physical properties of the wafers, namely aroma, texture, color, water absorption, and density, as well as rumen fluid characteristics, namely total volatile fatty acid (VFA), pH, and ammonia (NH3). The results showed that increasing storage duration tended to decrease total VFA from 123.12 ± 2.28 mM in T1 to 121.10 ± 2.01 mM in T4, although the values remained relatively stable. The rumen fluid pH was also relatively uniform, ranging from 6.82 ± 0.13 to 6.88 ± 0.13. NH3 concentration decreased with increasing storage duration, from 21.28 ± 0.54 mg/100 mL in T1 to 18.13 ± 1.51 mg/100 mL in T4. Storage duration had no significant effect (P>0.05) on the aroma, texture, or color of the wafers, indicating that their physical quality was maintained during storage. Based on these results, it can be concluded that complete feed wafers supplemented with mangrove fruit and PFAD maintained their physical quality and rumen fermentation stability for up to 60 days of storage.